548P A role of heparin-binding epidermal growth factor-like growth factor in myocardial involvement in immune-mediated necrotizing myopathy - Xu, L.; Meng-ge, Y.; Kosari, M.; Li, Y.; Bu, B.; Ji, S. (Neuromuscular disorders : NMD, 2024)
Heparin-binding EGF-like growth factor (HB-EGF) is a member of the EGF family which has been implicated in the pathogenesis of cardiac diseases, but their roles in immune-mediated necrotizing myopathy (IMNM) with myocardial involvement are unclear. In our study, we measured the serum HB-EGF levels of 30 patients with IMNM and 15 sex and age-matched volunteers admitted to the Neurology Department at Tongji Hospital between April 2013 and August 2022. Clinical data including patients’ demographics; laboratory test results and clinical characteristics (disease duration, muscle strength, atrophy, rash, dysphagia, dyspnoea, and myalgia) were collected from the clinical record system. A receiver operating characteristic (ROC) curve was drawn, and the area under the ROC curve was calculated to evaluate the diagnostic value of HB-EGF for cardiac involvement in IMNM. 30 patients showed a significant increase [110.4 (66.8 133.9) pg/ml verus 99.5 (80.5 127.7) pg/ml; p=0.013] compared with those of 15 normal subjects. Further analysis revealed 14 patients with IMNM whose cardiac abnormalities were notably up regulated [110.4 (66.8 133.9) pg/ml verus 136 (112.9 240.3) pg/ml; p=0.009] compared with 16 patients with IMNM without cardiac abnormalities based on cardiac magnetic resonance (CMR) examination. HB-EGF had a specificity and sensitivity of 100% and 40% respectively, at a cut-off value of 170.9 pg/ml for predicting myocardial injury in patients with IMNM. HB-EGF could be a promising non-invasive biomarker for diagnosing myocardial involvement in IMNM. However, a larger prospective study is warranted.